2017
DOI: 10.18393/ejss.318795
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient release dynamics of an accelerated compost: A case study in an Alfisol and Ultisol

Abstract: Article Info Received : 02.02.2017 Accepted : 22.05.2017 Acceleration of composting process could influence fertilizer-efficiency of the accelerated composts. This study therefore evaluated the nutrient release dynamics of different rates of a commercial accelerated compost (OBD-plus ) in two soils described as Alfisol and Ultisol, under laboratory incubation study, in order to generate information for simulation under field conditions. Accelerated compost (AC) at the rates of 30, 60, 90, 120, 150 kg N ha -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The N, P, K and S levels in four different types of amended compost are given in Table 2. Trichoderma was used for every MSW compost treatment (T3 -T10) in order to accelerate composting process (AyanfeOluwa et al, 2017). T. viridi inoculum was added to the amended and unamended MSW compost at a rate of 1 litre broth (liquid media) per ton compost, the fungal count being 10 6 cfu mL -1 .…”
Section: Methodsmentioning
confidence: 99%
“…The N, P, K and S levels in four different types of amended compost are given in Table 2. Trichoderma was used for every MSW compost treatment (T3 -T10) in order to accelerate composting process (AyanfeOluwa et al, 2017). T. viridi inoculum was added to the amended and unamended MSW compost at a rate of 1 litre broth (liquid media) per ton compost, the fungal count being 10 6 cfu mL -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Compost is reputed for not only its ability to increase soil aggregate stability, porosity, carbon, and plant nutrients but reduces the pH and risk of erosion [133]. In an incubation study carried out by AyanfeOluwa et al [134], amending Ultisol and Alfisol with conventional and accelerated composts increased the pH, carbon, N, P, and K compared with a conventional practice (NPK fertilisation only). In a field study that was carried out to determine the benefits of the combined use compost and zeolite on the fertility of organic-rich Mediterranean soils, the available K concentration significantly increased compared with the control and zeolite only [135].…”
Section: Compostmentioning
confidence: 99%
“…Although, the composting acceleration technology is relatively new in Nigeria, AyanfeOluwa et al (2017) found that the compost mineralized properly comparable to the conventional compost in an incubation study. In a further work, AyanfeOluwa (2019) also reported that nutrients from accelerated compost are also available for maize production comparable to conventional compost and mineral fertilizer in a screen house study.…”
Section: Introductionmentioning
confidence: 95%